AKTUALISASI MAKNA AL-TUHURU SHATRU AL-IMAN MELALUI BANK SAMPAH DALAM MENINGKATKAN KESEHATAN LINGKUNGAN - Mustabsyiratul Ailah; Muh. Ridwan (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2019)
Indonesia as a country with largest Muslim population in the world should be a role model country in all aspects specifically for environmental hygiene. Hygiene in Islamic teachings is the main priority, even in a hadith mentioned hygiene is part of faith. This means that the level of faith in a Muslim can be measured one of them through the aspect of hygiene reflected in himself and his environment. However, this contradiction in actualization with the fact that Indonesia was in the second position of the world’s largest plastic garbage contributor and National Geographic data stated that there were four rivers in Indonesia, including the 20 dirtiest rivers in the world. This paper aims to analyze the actualization of the meaning of the hadith al-Tuhuru Shatru al-Iman through the Waste Bank as an effort to improve environmental health in preventing the risk of disease occurring and utilization of waste in the economic field to achieve Indonesia Golden 2045. This writing method uses literature review by integrating various literatures of general science and Islamic teaching values. Based on a variety of literature studies it was concluded that Waste Banks are one of the alternative solutions that are efficient in improving environmental health as an actualization of the meaning of Islamic teaching values. Through the Waste Bank the community gets more effective waste management education, and the community as a customer gets benefits in terms of health and economic aspects